The Turks and Islam in Reformation Germany - Miller, Gregory J. (Professor of History), author.
1 online resource
Keywords: Although their role is often neglected in standard historical narratives of the Reformation, the Ottoman Turks were an important concern of many leading thinkers in early modern Germany, including Martin Luther. In the minds of many, the Turks formed a fearsome, crescent-shaped horizon that threatened to break through and overwhelm. Based on an analysis of more than 300 pamphlets and other publications across all genres and including both popular and scholarly writings, this book is the most extensive treatment in English on views of the Turks and Islam in German-speaking lands during this period. In addition to providing a summary of what was believed about Islam and the Turks in early modern Germany, this book argues that new factors, including increased contact with the Ottomans as well as the specific theological ideas developed during the Protestant Reformation, destabilized traditional paradigms without completely displacing inherited medieval understandings. This book makes important contributions to understanding the role of the Turks in the confessional conflicts of the Reformation and to the broader history of Western views of Islam.